In vitro toxicogenomic activity of an MTA/salicylate-based endodontic sealer - Leme, Kamila Sauer Veiga [UNESP]; Salvadori, Daisy Maria Fávero [UNESP] (Elsevier, 2022)
This study was designed to investigate whether mineral trioxide aggregate (MTA) Fillapex®, an MTA/salicylate-based endodontic sealer, exerts cytotoxic and toxicogenomic effects on human gingival fibroblasts (HGFs). HGFs were exposed in vitro to MTA Fillapex® at concentrations of 5%, 10%, 20%, and 40% for 24 h. Cytotoxicity, cell survival (5 days), cell cycle kinetics (flow cytometry), genotoxicity (comet assay), and gene (TP53, BAX, and BCL2) expression profiles were evaluated using reverse-transcriptase quantitative polymerase chain reaction. MTA Fillapex® was cytotoxic to HGFs at the two highest concentrations (20% and 40%), and cell survival decreased after 5 days treatment only with 40% concentration. After MTA Fillapex® treatment, there was an increase in the expression of apoptosis-related genes BAX, BCL2, and TP53, but no increase in DNA damage. Cement also induced changes in cell cycle kinetics, apoptosis, and necrosis rates. The data show the ability of MTA Fillapex® endodontic sealer to induce cellular and genetic alterations in HGFs. Our findings suggest that this compound should be used with caution to avoid health-related risks to the buccal tissue.
Keywords: Apoptosis; Cell cycle kinetics; Cytotoxicity; Gene expression; Genotoxicity; MTA Fillapex